2019
DOI: 10.1016/j.jid.2018.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Support for the Safe Use of Zinc Oxide Nanoparticle Sunscreens: Lack of Skin Penetration or Cellular Toxicity after Repeated Application in Volunteers

Abstract: Zinc oxide is a widely used broad-spectrum sunscreen, but concerns have been raised about the safety of its nanoparticle (NP) form. We studied the safety of repeated application of agglomerated zinc oxide (ZnO) NPs applied to human volunteers over 5 days by assessing the skin penetration of intact ZnO-NPs and zinc ions and measuring local skin toxicity. Multiphoton tomography with fluorescence lifetime imaging microscopy was used to directly visualize ZnO-NP skin penetration and viable epidermal metabolic chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
97
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(103 citation statements)
references
References 40 publications
(58 reference statements)
5
97
0
1
Order By: Relevance
“…The study concluded, however, that the penetration was concentrated mainly in the skin furrows and in support of Lin et al [15] also showed ZnO-NP exposure did not cause any cellular metabolic changes [14]. Mohammed et al showed the lack of skin penetration and cellular toxicity after repeated use of ZnO nanoparticles in volunteers [17,18].…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…The study concluded, however, that the penetration was concentrated mainly in the skin furrows and in support of Lin et al [15] also showed ZnO-NP exposure did not cause any cellular metabolic changes [14]. Mohammed et al showed the lack of skin penetration and cellular toxicity after repeated use of ZnO nanoparticles in volunteers [17,18].…”
Section: Introductionmentioning
confidence: 77%
“…Likewise, the biological material interacting with the nanoparticle surface, that is corona, will be completely different from that in cell culture [19]. Thirdly, there is a growing body of evidence showing that the stratified structure of skin forms an effective barrier against these nanoparticles in penetrating into deeper structures [10,17,18]. Because of the presence of the barrier and stratified cell layers, in vivo and 3D reconstructed skin models are the most relevant for cosmeceutical testing.…”
Section: Introductionmentioning
confidence: 99%
“…In the brain, the oxidative stress and inflammation reaction were found after ZnO NP exposure and more remarkable changes were identified in aged individual. These kinds of neurotoxicity might due to the destruction of the BBB integrity caused partly by ZnO NPs-induced systemic inflammation [135][136][137][138].…”
Section: Zinc Oxidementioning
confidence: 99%
“…In the brain, the oxidative stress and in lammation reaction were found after ZnO NP exposure and more remarkable changes were identi ied in aged individual. These kinds of neurotoxicity might due to the destruction of the BBB integrity caused partly by ZnO NPs-induced systemic in lammation [142][143][144][145].…”
Section: Zinc Oxidementioning
confidence: 99%